Development of learning media for shot put modification from ironwood material for physical education, sports, and health learning - Rahmad Rivalda; Imam Hariadi; Arief Darmawan (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
The objective of this study is to development of learning media for shot put modification from ironwood material for physical education, sports, and health learning at SMKN 1 Kota Besi. The research and development model follows the ADDIE procedure. Product testing will determine the feasibility of the developed product. Data is collected through observation and questionnaires for expert evaluations of learning, media, and practitioners. Data is also collected through small and large group testing and student assessments from tenth grade students at SMKN 1 Cempaga, SMKN 1 Kota Besi, and SMKN 2 Sampit. Quantitative descriptive statistical analysis is used for data analysis techniques. Based on the results of the analysis, learning experts scored 94%, media experts scored 96%, and practitioner experts scored 80%. The small-group trial at SMKN 1 Kota Besi showed a percentage of 90%, while the large-group trials at SMKN 1 Cempaga, SMKN 1 Kota Besi, and SMKN 2 Sampit showed percentages of 94%, 85%, and 76%, respectively. A comprehensive analysis of the research results shows that the development of modified shot put learning media made from ironwood for use in physical education, sports, and health education, particularly for class X students at SMKN 1 Kota Besi, is practical and feasible. This conclusion is based on the results observed when applying physical education, sports, and health teaching materials for shot put athletics.